2021
DOI: 10.3892/etm.2021.10790
|View full text |Cite
|
Sign up to set email alerts
|

Non‑alcoholic fatty liver disease and hematologic manifestations (Review)

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a multisystem disease, and it is associated with numerous extra-hepatic manifestations or additional co-occurring diseases. The aim of the present review was the identification and management of the hematologic manifestations of NAFLD. One of the triggers is considered to be iron abnormalities. Increased ferritin levels, hepatic iron deposits and iron overload are associated with NAFLD. The iron overload degree and severity are associated with the level of liver fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…It is called dysmetabolic iron overload syndrome (DIOS), which occurs in 15% of patients with MS and half of patients with NAFLD [2,23] . It is known that excessive iron can stimulate the secretion of in ammatory factor TGF-β1, which promote the activation of hepatic stellate cells (HSC, α-SMA is the activation marker) as a pro-brotic cytokine [24] , cause ECM accumulation and collagen deposition, aggravate liver damage, and nally lead to liver brosis [25,26] , cirrhosis and hepatocellular carcinoma [27,28] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is called dysmetabolic iron overload syndrome (DIOS), which occurs in 15% of patients with MS and half of patients with NAFLD [2,23] . It is known that excessive iron can stimulate the secretion of in ammatory factor TGF-β1, which promote the activation of hepatic stellate cells (HSC, α-SMA is the activation marker) as a pro-brotic cytokine [24] , cause ECM accumulation and collagen deposition, aggravate liver damage, and nally lead to liver brosis [25,26] , cirrhosis and hepatocellular carcinoma [27,28] .…”
Section: Discussionmentioning
confidence: 99%
“…Ferritin is made up of ferritin light chain (FTL) and FTH. FTH has iron oxidase activity, which converts Fe 2+ into Fe 3+ when iron enters the ferritin shell, while FTL promotes the formation of iron core storing Fe 3+ , and reduces the content of free iron [27] . When iron is de cient, Fe 3+ is released from ferritin and reduced to Fe 2+ again, and then Fe 2+ is exported to the extracellular space by FPN1 [36] for metabolism of other cells in the body.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of coagulation abnormalities in individuals with MASLD/metabolic dysfunction-associated steatohepatitis (MASH) highlights the intricate relationship between liver dysfunction and the mechanism of hemostasis [17,58]. Within the framework of metabolic dysfunction, it was reported that hepatic damage could contribute to the initiation of coagulation, hence inducing the initiation of fibrogenesis [28,58,63] and vice versa [16,18,62,64]. The liver plays a significant role in the regulation of hemostatic balance and in the synthesis of coagulation factors, which have been shown to diminish as liver fibrosis advances [65].…”
Section: Coagulation Dysfunctionsmentioning
confidence: 99%
“…Гематологические проявления НАЖБП включают синдром дисметаболической перегрузки железом (СДПЖ). СДПЖ характеризуется стеатозом, умеренным отложением железа в тканях, и повышенным уровнем ферритина в сыворотке крови при нормальном насыщении трансферрина сыворотки железом [3,4].…”
Section: Introductionunclassified